Nucleolar organiser regions in kidney tumours and xanthogranulomatous pyelonephritis. Issue 2 (February 1990) - Bryan, R L; Crocker, J; Farr, A
Abstract : The AgNOR argyrophil technique was applied to clear cut examples of renal adenoma (n = 7), clear cell carcinoma (n = 9), and xanthogranulomatous pyelonephritis (n = 5). There was no significant difference between mean AgNOR counts per cell in adenomas and carcinomas, supporting the idea that there is a continuous spectrum of kidney tumours. Xanthogranulomatous pyelonephritis and clear cell carcinoma showed significant differences in mean AgNOR counts per cell, suggesting that the technique may be of use in distinguishing between these conditions, although further cases may need to be examined to confirm this.